2022
DOI: 10.3390/s22030758
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Raman Amplification for Fiber Nonlinearity Compensation in a Mid-Link Optical Phase Conjugation System

Abstract: In this paper, we review different designs of distributed Raman amplifiers which have been proposed to minimize the signal power profile asymmetry in mid-link optical phase conjugation systems. We demonstrate how the symmetrical signal power profiles along the fiber can be achieved using various distributed Raman amplification techniques in the single-span and more realistic multi-span circumstances. In addition, we show the theoretically predicted results of the Kerr nonlinear product reduction with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…At the same time, distributed amplification allows for a precise control of signal power variation across transmission fibre [ 24 ], which is necessary to minimize asymmetry for the OPC system. In our previous works [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ] we compared several designs of distributed Raman amplifiers: first order, second order and dual order using bi-directional and backward-only pumping schemes. Bi-directionally pumped distributed Raman amplification with a single FBG at the end of the transmission span performed best in terms of asymmetry [ 24 ] and relative intensity noise (RIN) [ 30 , 31 , 32 ], which is a key design feature for data transmission in a 60 km span, hence we continue with this design and modifications to meet our bandwidth requirement.…”
Section: Amplifier Design For Optical Phase Conjugationmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, distributed amplification allows for a precise control of signal power variation across transmission fibre [ 24 ], which is necessary to minimize asymmetry for the OPC system. In our previous works [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ] we compared several designs of distributed Raman amplifiers: first order, second order and dual order using bi-directional and backward-only pumping schemes. Bi-directionally pumped distributed Raman amplification with a single FBG at the end of the transmission span performed best in terms of asymmetry [ 24 ] and relative intensity noise (RIN) [ 30 , 31 , 32 ], which is a key design feature for data transmission in a 60 km span, hence we continue with this design and modifications to meet our bandwidth requirement.…”
Section: Amplifier Design For Optical Phase Conjugationmentioning
confidence: 99%
“…For example, in [ 15 , 16 ], the fiber nonlinearity compensation using a mid-link OPC can be achieved using a symmetrical chromatic dispersion slope or effective management of dispersion mapping before and after the OPC. Alternatively, in [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], with a purposefully designed distributed Raman amplification scheme, a symmetrical signal power profile along the fiber before and after the OPC was demonstrated to maximize the effectiveness of nonlinearity compensation with a mid-link OPC. In [ 24 ], we numerically optimised the in-span signal power asymmetry for three different advanced Raman amplification schemes using a single channel in the middle of the C-band at 1545 nm and identified that the second-order distributed Raman amplification based on a single-side FBG random distributed feedback laser is the most convenient design to achieve the best signal power profile symmetry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, dispersion management is limited because it cannot completely compensate for the distortion caused by the nonlinear Kerr effect by itself. Meanwhile, optical phase conjugation is limited because it does not make the link configuration flexible, as the OPC must be in the middle or near the entire transmission link [15]. Furthermore, in the case of a WDM system, dispersion management has a problem that the wavelength of each channel is different, and as a result, it is difficult to compensate for the dispersion amount, which is accumulated differently depending on the wavelength of each channel [16].…”
Section: Introductionmentioning
confidence: 99%
“…Optical phase conjugator (OPC) in a long-haul transmission system can effectively compensate for both linear (e.g., chromatic dispersion) and nonlinear (e.g., the fiber Kerr nonlinearity) impairments, and therefore can improve the data capacity or transmission distance . The efficiency of how much the fiber nonlinearity can be compensated assisted by mid-link OPC was limited by several factors, such as the slope of the chromatic dispersion map of the transmission fiber and the signal power profile along the fiber [1][2][3][4][5][6]. The symmetry of chromatic dispersion slope can be tailored by optimizing the dispersion map using a combination of transmission fiber and dispersion compensating fiber [9].…”
Section: Introductionmentioning
confidence: 99%